2003
DOI: 10.1177/1051228402239719
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral and Systemic Hemodynamics Changes During Upright Tilt in Chronic Fatigue Syndrome

Abstract: The results of this study are not consistent with the hypothesis that patients with CFS have a distinctive pattern of MCA CBFV changes in response to orthostatic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
2
4
0
Order By: Relevance
“…Deficits in these regions may correlate to the persistent visceral symptoms experienced in CFS. The general trend for lower BOLD signal at rest in CFS compared to controls is consistent with the general reduction in cerebral blood flow and reports of orthostatic intolerance that are recurrent findings in CFS ( Razumovsky et al, 2003 ; Yoshiuchi, 2006 ; Pardini et al, 2010 ; Tajima et al, 2010 ; Biswal et al, 2011 ; Stewart et al, 2011 ; Ocon et al, 2012 ; Medow et al, 2014 ; Gay et al, 2016 ; Finkelmeyer et al, 2018 ; van Campen et al, 2020a , b , c ).…”
Section: Discussionsupporting
confidence: 87%
“…Deficits in these regions may correlate to the persistent visceral symptoms experienced in CFS. The general trend for lower BOLD signal at rest in CFS compared to controls is consistent with the general reduction in cerebral blood flow and reports of orthostatic intolerance that are recurrent findings in CFS ( Razumovsky et al, 2003 ; Yoshiuchi, 2006 ; Pardini et al, 2010 ; Tajima et al, 2010 ; Biswal et al, 2011 ; Stewart et al, 2011 ; Ocon et al, 2012 ; Medow et al, 2014 ; Gay et al, 2016 ; Finkelmeyer et al, 2018 ; van Campen et al, 2020a , b , c ).…”
Section: Discussionsupporting
confidence: 87%
“…These findings reject our hypothesis that a smaller CBF increase could explain the intolerance for physical exertion in CFS patients. This is in line with previous findings showing no altered CBF in CFS patients in supine position or in response to orthostatic stress (9,28). However, the study of Stewart et al (9) observed a lower absolute CBF velocity in response to incremental upright tilt combined with cognitive activation.…”
Section: E21supporting
confidence: 91%
“…Most studies of passive tilting to 60°demonstrate no change in mean arterial pressure (MAP) (Pawelczyk et al 1988;Sagawa et al 1993;Tuckman and Shillingford 1966) most likely due to the regulatory effects of baroreceptors. In contrast, two studies have found increased MAP, which would result in increased baroreceptor firing, with HUT (Laszlo et al 2001;Razumovsky et al 2003). However, data from animal studies suggest that this would reduce V T and f (Brunner et al 1982;Grunstein et al 1975;Saupe et al 1995).…”
Section: Possible Mechanisms For the Increase In Ventilation With Hutmentioning
confidence: 80%